UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INGGRIS MELALUI TASK-BASED LEARNING PADA SISWA KELAS XII IPS.2 SMA N 1 TALAMAU - Susiati, Lis (Jurnal Manajemen Pendidikan, 2017)
Based on the results of students study Class XII IPS.2 SMA N 1 Talamau in English subjects found that the results of student learning in English subjects is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about Improvement Efforts of student learning outcomes in sub English subjects Express the meaning and step retrika in the essay by using the variety of written language accurately, fluently and acceptable in the context of everyday life in text form: explanation Through Task-based Learning in Class XII IPS.2 SMA N 1 Talamau Kabupaten Pasaman Barat. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. Research subjects consisted of 26 students of Class XII IPS.2 SMA N 1 Talamau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been proposed, it can be concluded that Task-based Learning can improve student learning outcomes in sub English subjects Express the meaning and step retrika in the essay by using variety of written language accurately, fluently and acceptable in the context of daily life -day in text shaped: explanation in SMA N 1 Talamau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle is 57.38 (Enough) increased to 83.77 (Good) with an increase of 26.38%.